Thin-films and transistors of p-ZnTe. (February 2016) - Lastra, G.; Olivas, A.; Mejía, J.I.; Quevedo-López, M.A.
Highlights: ZnTe TFTs doped in 15 mg Cu solution showed linear and saturation regions. Maximum mobility was 10 −2  cm 2 /V s for TFTs with W / L  = 40/20, 40, 80 and 80/20 μm. Drain-currents from 10 −8 to 10 −9  A at V G  = 0 V were obtained in (35 nm) ZnTe TFT. Mobility in 75 nm p-ZnTe TFTs was higher than mobility in 35 nm p-ZnTe TFTs. Abstract: In this article, we report ( I DS – V DS ) characteristics of (75 and 35 nm) p-type ZnTe thin-film transistors (TFTs) at different active channels by photolithography. In 75 nm p-ZnTe TFTs, the source and drain contacts were doped with Cu in 11, 13 and 15 mg (Cu(NO3 )2 –3H2 O)/150 ml (H2 O) for 60 s and heated at 300 °C for 10 min. TFTs immersed in 15 mg solution showed the clearest linear and saturation regions, as well as an approximate mobility from 10 −2 to 10 −4  cm 2 /V s. Also, drain- currents ( I DS ) from 10 −8 to ∼10 −7  A were shown at V G  = 0 V (OFF-state). However, drain-current in the OFF-state decreased in 35 nm p-ZnTe TFTs. The films showed the cubic phase and the Cu1.44 Te-like orthorhombic phase.